Verb Phrase Mistakes in English Literature Students' Writing Composition - Rullyanti, Merry; Diana, Eli; Lestari, Noni Dwinka; Thoyyibah, Isthi Mawar (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
Examining the students’ errors on writing is part of the evaluation in English language learning and teaching. To produce a good writing, the English language learners have to be able to know the rules of the language use. This research aims to diagnose the errors with subject verb agreement made by the students as well as to explore the factors contribute the errors. To obtain the data, the researcher employed a document analysis and a semi-structure interview. The findings showed most of the errors belonged to misinformation category (33%) and were subsequently followed by omission category (29%) and addition category (29%) and misformation (9%). In addition, from the interview the researcher also found three major factors contribute the students’ errors, namely ignorance the editing process, the unawareness of the grammar rules, and intralingual errors. Keyword: Grammatical Errors, Subject-Verb Agreement, Writing, descriptive text